Outcomes of a Modified Technique for Successful Pneumatic Dissection in Pediatric Eyes With Corneal Scars. Issue 7 (July 2019) - Mattioli, Leila; Weiss, Jayne S.; Spena, Rossella; Leon, Pia; Myerscough, James; Bovone, Cristina; Busin, Massimo
Abstract : Purpose: To report the outcomes of a modified deep anterior lamellar keratoplasty (DALK) procedure for the treatment of scarred corneas in otherwise healthy pediatric eyes. Methods: All pediatric eyes undergoing DALK by the same surgeon (M.B.) between July 2013 and June 2017 were enrolled. The standard DALK procedure was modified by including a large (9 mm) and deep (150 μm from the thinnest pachymetric measurement) trephination, a minimal cannula advancement from the base of the trephination, and a clearing of a central 6 mm optical zone. The success rates of pneumatic dissection, visual and refractive outcomes, and complications were reported. A complete ophthalmologic examination was performed preoperatively and a few days after suture removal (6-months post-DALK) for all patients as well as 12, 24, and 36 months postoperatively for available patients. Results: Fourteen eyes of 13 patients with various indications were included in this study. The mean age at the time of surgery was 11.7 ± 2.5 years. Pneumatic dissection succeeded in all but one case (13/14 eyes = 92.8%), which was completed by hand dissection. All sutures were removed within 6 months of surgery. With a minimum postoperative follow-up of 6 months, best spectacle-corrected visual acuity improved from ⩽20/50 to ≥20/40 in all but one eye, which was known to be amblyopic. Conclusions: Despite impaired corneal transparency and increased tissue consistency, a modified DALK technique allows successful pneumatic dissection in an extremely high percentage of scarred pediatric eyes. Visual results compare favorably with those obtained in children after penetrating keratoplasty, while vision threatening complications are minimized.